Preclinical Development of a Prototype Protoplasmic Sonicate Protein Mucosal Vaccine PSPMV of Salmonella Typhi in A Lapin Model - Shnawa, Ibrahim M S; ALmmar, Mahdi H M (British Journal of Healthcare and Medical Research, 2023)
Protein based mucosal vaccines of human communicable bacterial diseases are being within the current reasearch mode.The presnt work was aimed at the preclinical development of a prototype protoplasmic sonicate proteinPSP mucosal vaccinePSPMV for human typhoid via lapin live challenge model.From a local confirmed S typhi vaccine seed strain,a dense cell biomass was prepared and sonicated by cell sonicator .The resultant sonicate protein was considered as prototype vaccine.An amount of 3mg/ml. Of the PSPMV was injected through SC route to five rabbits followed by one week leave then eviscerated for gross and histologic changes.It was found to be safe.Then fifeteen rabbits were divided into three groups each of five.Group I was primed per Os with five doses of 3 mg PSP each in 5ml. saline, in a week a part follwed by sixth week leave.Group II received IFA through SC route for one week followe by one week leave.Group III received 5ml saline per OS using same group I schedule.Three days after the leave week.Live S.typhi suspension of 1.5x 10 to 5 CFU/ml.,completed to 5ml in sterile saline were applied per Os to the three groups.Humoral agglutinin and heagglutinin responses wererised up to clinical titre limits were noted.In addition to significant leukocyte inhibitory factor response in challenged PSPMV group.Erythema,induration,necrosis were noted in skine DTH test of PSPMV group in a wister rat model.Survival record after challenge were 5/5 100% in PSPMV group, 4/5,80% in FIA group and 0/5 0% in saline control group.The novelity in this acheivement that PSPMV prototype S typhi showed 100% protection in rabbits,while OMP28 KDA vaccine was immunogenic but non-immune protective in awork done by other workers.These results are being promising but still need to be supported by developing a non-human primate challenge model.